(untitled) - Mitsubishi Corporation (New York, 1988)
This alphabetically arranged glossary of more than five hundred Japanese business terms provides American managers with an understanding of the Japanese corporate value system and operational modes.
Keywords: Japan,Nhật Bản; Commerce,Thương mại